SMART RAINWATER ALERT AND PREDICTION SYSTEM BASED ON MACHINE LEARNING AND SENSOR INTEGRATION - Aggarwal, Anmol; Kushaggr; Kumar, Abhay; Yash; Rawat, Trilok (International Journal of Engineering Technologies and Management Research, 2022)
This project presents the development of a Rain Prediction and Alarm Circuit system that combines real-time rain detection hardware with advanced predictive modeling using Prophet and Long Short-Term Memory (LSTM) networks. The primary objective is twofold: immediate detection of rainfall using a rain sensor circuit and accurate short-term forecasting of rain patterns to enable proactive water conservation and resource management. The hardware component utilizes a rain sensor module integrated with a 555 Timer IC configured in monostable mode. Upon detecting rain droplets, the sensor triggers the timer, activating an audible alarm via a buzzer, thereby providing instant notification to users. This enables quick actions such as deploying rainwater harvesting mechanisms, protecting outdoor equipment, or alerting agricultural systems. The simple, cost-effective, and reliable design ensures suitability for everyday life, manufacturing processes, smart irrigation, and home automation. Complementing the hardware, machine learning models are employed to forecast rainfall trends. Prophet, a robust time series forecasting tool developed by Facebook, is used to model seasonal and trend components, while an LSTM network captures complex temporal dependencies in historical rainfall data. By combining these models, the system provides both immediate rain detection and predictive analytics, empowering users to plan irrigation schedules, optimize water storage, and enhance disaster preparedness. Overall, this integrated rain detection and prediction system not only addresses the need for timely responses to rainfall events but also promotes sustainable water usage practices. Its scalability, low cost, and dual functionality make it ideal for applications in agriculture, smart homes, environmental monitoring, and automated weather response systems.